ANALISIS PERAN PARTAI POLITIK LOKAL DALAM PENGENTASAN KEMISKINAN DI MEULABOH KABUPATEN ACEH BARAT - T. Argya Amanda; Augustin Rina Herawati; Teuku Afrizal (Journal of Public Policy and Management Review, 2023)
Dewan Pimpinan Wilayah (DPW) Partai Aceh (Aceh Party) West Aceh Regency is one of the large organizations that is very influential and plays a strategic role in West Aceh Regency, so this makes the DPW-PA West Aceh Regency play a role in poverty alleviation and improving people's welfare in West Aceh Regency. The high level of poverty percentage in West Aceh Regency in 2021 is 18.81% so that it is in seventh position out of 23 Regencies/Cities in Aceh Province. This is influenced by several factors, so that the poverty rate that occurs in West Aceh Regency increases by 0.47% in 2021. This study aims to describe and determine the role and supporting and inhibiting factors of the West Aceh Regency DPW-PA in poverty alleviation in West Aceh Regency. This study uses qualitative methods, data collection techniques by interviews and observation and documentation, data sources using primary and secondary data. The results showed that the West Aceh Regency DPW-PA played a very good role as a coordinator, facilitator, accelerator, policy creator and implementer in poverty alleviation in West Aceh Regency. However, there were several factors inhibiting the role, namely internal problems and gaps between members.